PERANCANGAN ILUSTRASI DIGITAL “TOKOH WANITA DALAM MASALAH RASISME DAN SEKSISME” DARI BRAND 2MADISON AVENUE - Petrus, Okki Sugiharto; Haeril, Fachmi Khadam (Anggada : Jurnal Desain dan Seni, 2021)
“2madison Avenue” is a fashion brand that uses digital illustrations as a media strategy for delivering messages and also as a visual attraction to lift and increase public interest in the development of art and global history, especially among young people. The problems that are happening in the community are also often packaged in their entirety in fashion designs. The main purpose of designing this digital illustration of "Women’s Figures in the Problem of Racism and Sexism" this as a communication and campaign media that is packaged by visualizing the problems of Racism and Sexism that occur in the community into an illustration. It is hoped that this illustrative work can match the intended target to raise public interest in local products, as well as a campaign to raise awareness to the public about differences. And to remind people of existing human values without racism.